2016
DOI: 10.1007/s13224-015-0838-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Near Miss: A Valuable Contribution in Maternal Care

Abstract: Background MMR has always been recognized as an important indicator of quality of health services. The MMR in India has so far not reached up to the required MDG 2015. If we look into this matter with the eagle's eye view, then there are certain gray areas which need attention. For this, it is not the maternal mortality but the maternal near miss which has to be focused. Objectives To audit the maternal near miss in our institution and to review the pathways that lead to severe maternal morbidity and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
4
11
1
Order By: Relevance
“…Near miss death ratio was found to be 3.1:1 which means that for every three MNM women, one woman dies of complications. In the present study, near miss: death ratio was found somewhat similar to other studies,[51417] while in some other states, it was found to be higher. [41316] Higher near miss mortality ratio indicates a better quality of care at that facility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Near miss death ratio was found to be 3.1:1 which means that for every three MNM women, one woman dies of complications. In the present study, near miss: death ratio was found somewhat similar to other studies,[51417] while in some other states, it was found to be higher. [41316] Higher near miss mortality ratio indicates a better quality of care at that facility.…”
Section: Discussionsupporting
confidence: 92%
“…It was higher in other studies compared to the present study. [417] Higher the index, more women with life-threatening conditions will die. However, it was found to be lower in some states than the present study, which indicate more deaths of women at our study hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality index in our study is comparable to study done by Singh et al 16 with mortality index of 32.58, while study done by Madhvi et al 17 found the index of 8.3. The higher the index the more women with life threatening conditions die (low quality of care), whereas the lower the index the fewer women with life threatening conditions die (better quality of care).…”
Section: Discussionsupporting
confidence: 89%
“…Hypertension and haemorrhage were the main cause of maternal near miss. 8 Similar study by Chhabra P, the leading cause of MNM were haemorrhage, hypertension and sepsis. 9 In a study by Kalra P et al, near miss incidence was 4.18/1000 LB.…”
mentioning
confidence: 52%